2019
DOI: 10.1186/s12888-019-2170-z
|View full text |Cite
|
Sign up to set email alerts
|

Over-connected? A qualitative exploration of smartphone addiction among working adults in China

Abstract: Background Smartphones currently dominate people’s lives and interests due to their increased affordability and functionality. However, the negative aspects of smartphone use, such as smartphone addiction, have recently been brought up. This study utilized a qualitative approach to explore the symptoms of smartphone addiction among working adults in China and the psychological factors that affect such addiction. Methods Semi-structured interviews, either face to face or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…This class of behaviors is strongly related to the current use of the smartphone as the prominent device for Internet access. Furthermore, they allow people to install various applications and utilities to perform numerous activities according to personal needs and interests (Li & Lin, 2019). Regarding shopping addiction, a meta-analysis (Maraz et al, 2016) reported a pooled prevalence in the adult population of 4.9%, in line with our findings; however, the authors highlighted a variation in prevalence between samples due to the different instruments as well as the inclusion of new strategies of buying (e.g., online shopping).…”
Section: Discussionsupporting
confidence: 82%
“…This class of behaviors is strongly related to the current use of the smartphone as the prominent device for Internet access. Furthermore, they allow people to install various applications and utilities to perform numerous activities according to personal needs and interests (Li & Lin, 2019). Regarding shopping addiction, a meta-analysis (Maraz et al, 2016) reported a pooled prevalence in the adult population of 4.9%, in line with our findings; however, the authors highlighted a variation in prevalence between samples due to the different instruments as well as the inclusion of new strategies of buying (e.g., online shopping).…”
Section: Discussionsupporting
confidence: 82%
“…Recent research has suggested that addiction should be widened to cover a broader range of behaviours (Chen, 2020;Young, 2010 (Griffiths, 1998;Panova & Carbonell, 2018;Panova, Carbonell, Chamarro & Puerta-Cortes, 2020). Some researchers have observed mobile phone users and found symptoms of addiction such as withdrawal, salience, phantom phone signals (Li & Lin, 2019) and anxiety (Ha, Chin, Park, Ryu & Yu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Billieux, Maurage, Lopez-Fernandez, Kuss and Griffiths (2015) and Panova and Carbonell (2018) proposed using other terms such as 'problematic use' when studying excessive use and the negative (Griffiths, 1998;Panova & Carbonell, 2018;Panova, Carbonell, Chamarro & Puerta-Cortes, 2020). Some researchers have observed mobile phone users and found symptoms of addiction such as withdrawal, salience, phantom phone signals (Li & Lin, 2019) and anxiety (Ha, Chin, Park, Ryu & Yu, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Teknolojinin gelişmesiyle birlikte geleneksel telefonlar dönüşüme uğramış ve işlevsellik kazanarak telefonla konuşmanın dışında birçok ihtiyacımızı karşılar hale gelmiştir [36]. Bankacılık işlemlerinden navigasyona, sosyal iletişimden eğlenceye kadar çeşitli birçok alanda kullanılan akıllı telefonlar artık günlük yaşantının bir vazgeçilmezi olmuştur [24,8]. Artan işlevsellikleri ile hayatı daha kolay bir hale getiren akıllı telefonların hem kullanıcı sayıları hem de kullanım süreleri önemli bir artış göstermiştir [11].…”
Section: Gi̇ri̇ş (Introduction)unclassified